2012
DOI: 10.1097/scs.0b013e31824ddf5a
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Transfer of 2 Paddles of Thoracodorsal Artery Perforator Flap With 1 Pair of Vascular Anastomoses for Barraquer-Simons Syndrome

Abstract: We report a novel technique: a 1-stage transfer of 2 paddles of thoracodorsal artery perforator (TAP) flap with 1 pair of vascular anastomoses for simultaneous restoration of bilateral facial atrophy. A 47-year-old woman with a severe bilateral lipodystrophy of the face (Barraquer-Simons syndrome) was surgically treated using this procedure. Sufficient blood supply to each of the 2 flaps was confirmed with fluorescent angiography using the red-excited indocyanine green method. A good appearance was obtained, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…We often use LD flaps for secondary reconstruction after head and neck surgery 19–11,13 . They are versatile and can augment extensive depression and smile reanimation because they can be divided into components with a single vascular pedicle by branching of the thoracodorsal vessel and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…We often use LD flaps for secondary reconstruction after head and neck surgery 19–11,13 . They are versatile and can augment extensive depression and smile reanimation because they can be divided into components with a single vascular pedicle by branching of the thoracodorsal vessel and nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ICG fluorescent angiographic images confirmed the perfusion of nerves in ALT flaps. We previously used ICG fluorescence angiography to monitor blood flow 14,15 because it allows clear and safe visualization of blood flow and is minimally invasive, cheap, and easy to prepare. Adverse reactions to the infusion of ICG (e.g., nausea or anaphylactic shock) are potential risks, but their incidence is very low (less than 0.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, turning the length to width of the bi-paddle flap enables primary closure of the donor site. There are several reports regarding the clinical application of the bi-paddle flap, such as the bi-paddle radial artery flap (6), the double skin paddle ALT flap (7,8) and the bi-paddle thoracodorsal artery flap (9). It provides bespoke cover for large soft-tissue defects with improved morbidity and cosmesis of the donor site; more tissue can be harvested because of the multiple perforators (8).…”
Section: Introductionmentioning
confidence: 99%